Respostas bioeconômicas de sistemas de terminação de cordeiros do grupamento genético pantaneiro - Batista, Nielyson Junio Marcos (2015)
The aim of this study was to evaluate the productive performance and carcasses quantitative characteristics and economic viability of lambs of the Pantaneiro genetic group in four production systems: 1) grazing B. brizantha cv Piata, sealed protein and energy supplementation supplied in a proportion of 2% body weight (SEL); 2) grazing B. brizantha cv Piata intercropped with sorghum and protein and energy supplementation supplied in a proportion of 2% body weight (CLI); 3) Confinement with protein and energy supplementation supplied in a proportion of 2% body weight and sorghum silage in the ratio of 1.5% of body weight (COF2); and 4) Confinement with protein and energy supplementation supplied in a proportion of 4% body weight and sorghum silage in the ratio of 1.5% of body weight (COF4). We used 100 lambs with 17.85 ± 2.50 kg of body weight and 70 ± 15 days of age. A completely randomized design was used, with four finishing systems and twenty-five animals per system. Animals were weighed fortnightly for protein and energy supplementation feed adjustment. The duration of the experiment was determined by the time required for animals to accumulate two millimeters thickness of subcutaneous fat. Economic analysis was based on the calculation of gross margin, and variable costs and gross revenues the basis of economic analysis. Experimental systems generated scenarios for assessing economic viability. Average values of final body weight and total weight gain in the animals finished under CLI were higher when compared to the values obtained in COF2, while in SEL and COF4 finish systems these characteristics did not differ (P> 0.05). Lambs finished in SEL, CLI and COF4 had the highest average of hot and cold carcass weight compared to animals finished in COF2. Nevertheless, higher yields of hot and cold carcass have been identified in animals finished in COF4. We identified significant difference (P <0.05) for carcass compactness index in animals finished in COF4 with higher values than those observed in animals finished in COF2. Evaluation of the economic results showed that there were economic return for the termination systems, except for COF2, and the termination of lambs in Crop- Livestock Integration were more profitable. Therefore, based on the conditions under which the study was conducted, and according to the analyzes and discussions presented in this work we concluded that: the CLI for providing forage and grain production combined with livestock activity, requiring smaller area for termination lambs and weight gain similar to other systems, was the system better economic results and is indicated as an option for termination of lambs in the Midwest region of the Country.